ETYMOLOGY OF SOME TERMS AND CONCEPTS BELONG TO RELIGIOUS TOURISM (Texas Journal of Multidisciplinary Studies, 2021)
The article gives examples of some terms and concepts related to types of tourism, including religious tourism, such as the origin of the term pilgrimage, religious, excursion, travel, religious research, language, history, content, definition and etymology